PENGARUH PENGGUNAAN INTAKE MANIFOLD DENGAN BAHAN DASAR KOMPOSIT (SERAT NANAS) TERHADAP KONSUMSI BAHAN BAKAR DAN EMISI GAS BUANG PADA SEPEDA MOTOR HONDA SUPRA X 125 TAHUN 2007 - Purnomo, Bayu Gilang (Jurnal Nosel, 2015)
The objective of this research is to investigate the fuel consumption and exhaust emission of Motorcycle Honda Supra X 125 assembled in 2007 with the use of intake manifold with base material ofpineapple leaf composites. This research used the experimental method. Its sample was Motorcycle Honda Supra X 125 assembled in 2007 with Machine Number: JB51E1951246. The sample of research was taken by using the purposive sampling technique. The data of research were gathered through experimental method. The fuel consumption was measured in a static condition with measuring cup. The testing was done by measuring the time required by the machine to spend fuel in a certain volume at the low, medium, and high machine revolutions. The measurement of exhaust emission of carbon monoxide (CO) and hydrocarbon (HC) used the gas analyzer of Type 898 OTC STARGAS Global Diagnostic, which was conducted according to SNI 09-7118.3-2005 regarding Procedure for Testing Motor Vehicle with L category in idle condition. The data of research were analyzed by using the descriptive comparative technique of analysis. The results of research show that the average fuel consumption in the use of standard intake manifold at the machine revolutions of 1.200 rpm, 2.500 rpm, and 4.000 rpm is 0.088256 ml/second. Meanwhile the average fuel consumption in the use of intake manifold with pineapple leaf fiber composites at the machine revolutions of 1.200 rpm, 2.500 rpm, and 4.000 rpm is 0.072183 ml/second. Thus, the average fuel consumption in the use of intake manifold with pineapple leaf fiber composites decreases up to 20.7%. In addition, the average exhaust emission of CO in the use of standard intake manifold is 1.838%. Meanwhile, the average exhaust emission of CO in the use of intake manifold with pineapple leaf fiber composites is 1.127%. Accordingly, the average exhaust emission of CO in the use of intake manifold with pineapple leaf fiber composites decreases up to 38.7%. Furthermore, the average exhaust emission of HC in the use of standard intake manifold is 1.178 ppm. Meanwhile, the average exhaust emission of HC in the use of intake manifold with pineapple leaf fiber composites is 1.141 ppm. Therefore, the average exhaust emission of HC in the use of intake manifold with pineapple leaf fiber composites decreases up to 3.1%.